A RESEARCH ON SEED PROPAGATION OF Cunninghamia konishii HAYATA AT THE NURSERY - Dang, Ngoc Huyen; Hoang, Thi Thu Trang; Vu, Dinh Duy; Nguyen, Van Sinh; Do, Thi Tuyen; Pham, Thi Ly; Pham, Mai Phuong (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A RESEARCH ON SEED PROPAGATION OF Cunninghamia konishii HAYATA AT THE NURSERY Cunninghamia konishii Hayata has not only ecological importance in the forest ecosystem but also great commercial value in timber and fragrant essential oil. Them listed it as endangered in Red Book of Vietnam and IUCN Red List. This species naturally grows at an altitude of 1,200-1,600 m on the humus alpine and species also lives together with other species conifer such as Fokienia hodginsii, Amentotaxus argotaenia and Podocarpus spp.,… C. konishii was poor regeneration status. The paper presents the results of seed propagation and growth of C. konishii at the nursery stage. The result shows that the seed purity was 70.3% after 35 days. Seeds were treated and soaked in warm water at 60oC for the highest germination rate of 30.3%. Seedlings grew quickly and evently in a potting mix of 10% muck and 2% superphosphate. The formula of 25% shading for the growth of C. konishii in the nursery period up to 4 months of age is the best with a survival rate of 96%, growth height was 4.7 cm, diameter was 1.1mm. Our study will assist conservators in future conservation management, breeding, production and habitats restoration of the species.